2013
DOI: 10.3354/dao02580
|View full text |Cite
|
Sign up to set email alerts
|

Complex interaction between proliferative kidney disease, water temperature and concurrent nematode infection in brown trout

Abstract: Proliferative kidney disease (PKD) is a temperature-dependent disease caused by the myxozoan Tetracapsuloides bryosalmonae. It is an emerging threat to wild brown trout Salmo trutta fario populations in Switzerland. Here we examined (1) how PKD prevalence and pathology in young-of-the-year (YOY) brown trout relate to water temperature, (2) whether wild brown trout can completely recover from T. bryosalmonae-induced renal lesions and eliminate T. bryosalmonae over the winter months, and (3) whether this rate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…In fact, we observed a significant increase in T. bryosalmonae prevalence in 1+ and older fish for the whole data set (Wilcoxon signed ranks test) as well as for 4 individual comparisons (2×2 contingency table). These results are in line with a recent study by Schmidt-Posthaus et al (2013), who found a similar pattern of high T. bryosalmonae prevalence in 1+ trout in a Swiss river system. According to SchmidtPosthaus et al (2013), the pathological lesions in 1+ trout, such as acute gill and kidney lesions, indicate re-infection rather than proliferation of the remaining parasites.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…In fact, we observed a significant increase in T. bryosalmonae prevalence in 1+ and older fish for the whole data set (Wilcoxon signed ranks test) as well as for 4 individual comparisons (2×2 contingency table). These results are in line with a recent study by Schmidt-Posthaus et al (2013), who found a similar pattern of high T. bryosalmonae prevalence in 1+ trout in a Swiss river system. According to SchmidtPosthaus et al (2013), the pathological lesions in 1+ trout, such as acute gill and kidney lesions, indicate re-infection rather than proliferation of the remaining parasites.…”
supporting
confidence: 93%
“…According to SchmidtPosthaus et al (2013), the pathological lesions in 1+ trout, such as acute gill and kidney lesions, indicate re-infection rather than proliferation of the remaining parasites. It is therefore likely that a higher prevalence of T. bryosalmonae observed in this study was caused by re-infection of 1+ trout during the second summer while lack of clinical signs suggest partial immunity of 1+ fish (Schmidt-Posthaus et al 2013). 145 Dis Aquat Org 109: 139-148, 2014 We also detected T. bryosalmonae infection in the middle and posterior part of the kidney in 3 returning adult sea trout spawners.…”
Section: Tetracapsuloides Bryosalmonae Prevalence In 0+ and Older Fishmentioning
confidence: 68%
“…The fact that similar results were obtained testing higher temperature thresholds can be taken as a hint that infection is in fact related to extended periods of water temperatures higher than 15°C. Several other studies could not prove a correlation between temperature and site‐specific prevalence of T. bryosalmonae (Carraro et al., ; Schmidt‐Posthaus, Steiner, Müller, & Casanova‐Nakayama, ; Wahli, Bernet, Segner, & Schmidt‐Posthaus, ). Temperature data were not available from all rivers, especially data from some upstream locations are missing, which were free of the parasite and most likely exhibit low water temperatures.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, it is comprised of hematopoietic and lymphoid tissue, exerting immunological functions (Zapata et al 2006). The latest research on teleost kidney mainly focuses on the clinical aspects of infections, such as the bacterial kidney disease (Schmidt-Posthaus et al 2013), investigations on the expression of immune relevant genes in head kidney leukocytes (Villarroel et al 2013) and the regulation of cortisol release (Conde-Sieira et al 2013).…”
Section: Introductionmentioning
confidence: 99%